SOX9: a key transcriptional regulator in organ fibrosis - Li, Yishuo; Xing, Yue; Liu, Ning; Liu, Bin; Wang, Zhihui (Frontiers in Pharmacology, 2025)
The SOX9 gene locus is not only extensive but also intricate, and it could promote fibrosis in different organs or tissues, including cardiac fibrosis, liver fibrosis, kidney fibrosis, pulmonary fibrosis, as well as other organ fibrosis. Many disorders are associated with the process of fibrosis; moreover, fibrosis is a common symptom of chronic inflammatory diseases, characterized by the accumulation of excessive components in the extracellular matrix through different signaling pathways. The advanced stage of the fibrotic process leads to organ dysfunction and, ultimately, death. In this review, we first give an overview of the original structure and functions of SOX9. Second, we will discuss the role of SOX9 in fibrosis in various organs or tissues. Third, we describe and reveal the possibility of SOX9 as an antifibrotic treatment target. Finally, we will focus on the application of novel technologies for SOX9 and the subsequent investigation of fibrosis.